Mechanical and thermal properties of ginger (Zingiber officinale Rosc.) - R Visvanathan, E Jayashree, (Journal of Spices and Aromatic Crops, 2011)
Mechanical properties of fresh and stored (under ambient conditions for 2 months) ginger rhizomes (Zingiber officinale) (cv. Himachal) necessary for the design of processing machineries, were determined. Thermal properties were determined for fresh and dry ginger. Mechanical properties like peel penetration force for primary, secondary and tertiary finger rhizomes increased from 0.45 N, 0.52 N and 0.51 N to 0.60 N, 0.70 N and 0.65 N, respectively; the peel compressive force at rupture increased from 20.12 N, 19.86 N and 17.56 N to 22.58 N, 21.21 N and 19.67 N, respectively, and the cutting force required to penetrate through peel increased from 31.56 N, 27.68 N and 26.57 N to 32.71 N, 28.93 N and 28.16 N, respectively, in fresh and stored ginger rhizomes. Thermal properties like specific heat, thermal conductivity and thermal diffusivity for fresh ginger were 3566.87 J kg-1 K-1, 0.2916 W m-1 K-1 and 0.8609 x 10-7 m2 s-1 and the corresponding values for dry ginger at 10% moisture content were 1918.81 J kg-1 K-1, 0.0760 W m-1 K-1 and 1.7339 x 10-7 m2 s-1, respectively.